An Analysis of Temperature-Dependent Timing Jitter Factors in the Structural Design of Complementary Metal-Oxide-Semiconductor Single-Photon Avalanche Detectors - Jau-Yang Wu; Yu-Wei Lu; Meng-Hsuan Liu; Tien-Ning Chang; Chun-Hsien Liu (Sensors)
Single-Photon Avalanche Photodiodes (SPADs) are increasingly utilized in high-temperature-operated, high-performance Light Detection and Ranging (LiDAR) systems as well as in ultra-low-temperature-operated quantum science applications due to their high photon sensitivity and timing resolution. Consequently, the jitter value of SPADs at different temperatures plays a crucial role in LiDAR systems and Quantum Key Distribution (QKD) applications. However, limited studies have been conducted on this topic. In this study, we analyze the jitter characteristics of SPAD devices, focusing on the influence of device structures in two SPAD designs fabricated using the TSMC 18HV and TSMC 13HV processes. Using picosecond lasers with wavelengths ranging from ultraviolet (405 nm) to near-infrared (905 nm), we investigate the impact of different diffusion carrier types on jitter values and their temperature dependence across a range of 0 °C to 60 °C. Our results show that the jitter value of SPAD devices with low electric field regions varies significantly with temperature. This variation can be attributed to the higher temperature-dependent diffusion constant, as demonstrated by fitting the jitter diffusion tail with two diffusion time constants. In contrast, SPADs designed with modified electric field distributions exhibit smaller diffusion time constants and weaker temperature dependence, resulting in a much smaller temperature-dependent jitter value.